FIRQAH DALAM ISLAM: Pergeseran Nalar Politik ke Sistem Teologi - M Mibtadin (MAMBA'UL 'ULUM, 2020)
In the history of the development of Islamic thought since a long time ago there had been a split which was an embodiment of the words of the Messenger of Allah: Will this people be divided into 73 groups all in hell except one, then asked: who are they O Messenger of Allah? The Prophet replied: they are those who follow my Sunnah and the Sunnah of my best friend. (HR. At-Tirmidzy). From these hadiths and various political upheavals in Islam after the death of the Prophet Muhammad, then various systems of Islamic theological thought emerged. This shift of political thought to the religious thought system gave rise to the Khawarij, Shi’a, Sunni (Gahl as-Sunnah wal al-Jamaah), Murji’ah, and Mu’tazilah. His findings have a different paradigm of thinking about theological thought, even their religious thought systems are made as claims of justification for their respective political decisions.